Pedagogical assistance as a mechanism of socio-pedagogical adaptation of cadets of military universities - S. Yartsev (Вестник Северо-Кавказского федерального университета, 2023)
The relevance of the article is due to the increased relevance of high-quality training of cadets of military universities, as well as the need to search for new pedagogical concepts that ensure the effectiveness of pedagogical assistance and individual personal development. The purpose of this article is a theoretical analysis of the concept of "pedagogical assistance" in modern pedagogy. Materials and methods of research. The study is based on a theoretical analysis of the essence of the concept of "assistance" in the framework of socio-pedagogical adaptation of cadets of military universities. Research results and their discussion. After analyzing the different interpretations of approaches in the interpretation of the concept in pedagogy, we came to the conclusion that pedagogical assistance is of a humanistic nature and is conditioned by a number of conditions that help meet not only the educational needs of cadets, but also contribute to the realization of personal potential. We also analyze the components of pedagogical assistance: personal, cognitive, process, vector, adaptive. Conclusion. According to the results of the study, it can be concluded that the combination of all components gives a kind of integral education, which includes the desire for success at various personal levels, awareness in the development of new knowledge, the search for personal meanings, the productive implementation of personal choice, the preparation of a specific plan and its implementation of joint activities with subsequent reflection, an adaptive response the student. This material is intended for teachers of the education system of military universities, researchers and other interested persons.